Effect of antibiotic treatment on inflammatory markers and lung function in cystic fibrosis patients with Pseudomonas cepacia. - Peckham, D. (1994)
BACKGROUND--The acquisition of Pseudomonas cepacia in patients with cystic fibrosis is associated with increasing deterioration in lung function and more frequent hospital admissions. Pseudomonas cepacia is usually resistant to several antibiotics in vitro, but the response of patients colonised with the organism has not been extensively studied in vivo. METHODS--A three month prospective study was performed to investigate the response of 14 Ps cepacia positive patients and 10 Ps cepacia negative patients to a two week course of intravenous antibiotics. All those who were Ps cepacia negative and six of the 14 Ps cepacia positive patients had Ps aeruginosa in their sputum which was sensitive to the prescribed therapy. The inflammatory markers C-reactive protein, white blood cell count, serum lactoferrin, neutrophil elastase/alpha 1-antitrypsin complex, and tumour necrosis factor alpha were measured at the start and end of each antibiotic course. RESULTS--The median (range) % improvement in baseline FEV1 and FVC following treatment in the group as a whole was 15.2% (-23.5% to 156.3%) and 23.9% (-36.8% to 232.7%) respectively. There was no statistical difference in improvement in lung function, body weight, or inflammatory markers between individuals who were Ps cepacia positive and those who were Ps cepacia negative. CONCLUSIONS--Patients who are Ps cepacia positive appear to respond as well to intravenous antibiotics as those who are Ps cepacia negative, despite having lower lung function and a bacterium in their sputum which is resistant in vitro to the antibiotics used.